+0  
 
0
136
2
avatar

  Need some help with this please.

 

 

 Oct 24, 2018
 #1
avatar+27558 
+1

The question is: "What is the coefficient of a4b4 in the expansion of (a2/3 + 2b)6?"

 

In general: (x + y)6 = x6+6*x5*y+15*x4*y2+20*x3*y3+15*x2*y4+6*x*y5+y6

 

In your case x = a2/3 and y = 2b

 

I'm sure you can take it from here.

 Oct 24, 2018
edited by Alan  Oct 24, 2018
 #2
avatar
0

[6C2] X [a^2/3(First term of original binomial)]^(desired power(2)) X [2b(Second term of original binomial)]^(desired power(4)) 
(6C2 ) x (a^2/3)^2 x (2b)^4= 15 x a^4/9 x 16b^4=(15 x 16)/9a^4b^4=80/3a^4b^4

 Oct 24, 2018
edited by Guest  Oct 24, 2018

9 Online Users

avatar